A team task complexity measure for emergency procedures in fully automatic metro. (3rd October 2018) - Niu, Ke; Fang, Weining; Guo, Beiyuan
Summary: A measure of team task complexity for emergency procedures in fully automatic metro is proposed using a Euclidean norm based on two factors: internal complexity of network nodes Node com  −  inside and external complexity of network nodes Node com  −  outside . The development of the operation complexity measure followed four steps. First, team task complexity network for emergency procedures was constructed. Second, the task complexity (TC) method used as complexity measure of individual was adopted to measure the internal complexity of network nodes. Then, the external complexity of network nodes was measured by structure entropy. Finally, the team task complexity values for emergency procedures were determined by the Euclidean norm of the two factors. To verify the validity of this team task complexity measure, a one‐factor experiment was designed to test the proposed model. Thirteen team subjects participated in the experiment and performed 5 typical emergency scenes. Both objective indexes ( TeamTIME ) and subjective indexes ( TeamWORKLOAD and TeamSUBCOMPLEXITY ) were used in the experiment. The data analysis showed that the TeamTIME, TeamWORKLOAD, and TeamSUBCOMPLEXITY could be predicted well from the team task complexity value. The proposed team task complexity measure can be used for evaluation of emergency procedures design in fully automatic metro.